Pendampingan Prosedur Sertifikasi Tanah Wakaf bagi Pengurus Masjid dalam Membangun Kepastian Hukum dan Kemandirian Masjid - Abdillah, Nanang; Maftuh, Maftuh; Pristiwiyanto (Community: Jurnal Pengabdian Kepada Masyarakat, 2025)
Waqf land of mosques is a vital asset that plays a strategic role in supporting religious and social activities of the Muslim community. However, many mosque waqf lands in Menganti Subdistrict remain uncertified, making them vulnerable to disputes and legal issues. This study aims to assist mosque administrators (takmir) in understanding and managing the legal and procedural aspects of waqf land certification. The assistance employs a participatory approach focusing on empowering administrators through education, technical training, and administrative facilitation. The results show increased awareness and enthusiasm among mosque administrators in managing waqf land certificates, with active participation reaching 80 percent of total mosques in the area. The program successfully facilitated 16 mosques in the direct certification process. Continuation of this program is expected to foster professional, transparent, and sustainable waqf management, ensuring legal certainty and peace in mosque worship activities. These findings can serve as a model for other regions in improving waqf asset management.